Problematic Issues of Calculating the Size of Damage from the Use of Land Plots for Other Purposes within the Practice of Law Enforcement Agencies - I. V. Bryhadyr; I. V. Panova (Law and Safety)
The authors have studied the land legislation and the practice of its application in regard to the calculation of the amount of damage from the use of land plots for other purposes. The method of calculating the amount of damage from the specified use of land plots has been improved.